The Importance of Monitoring Actions in Reverse Logistics: National Overview, CETESB (SP) Success Story and Initiatives in the State of Santa Catarina - Bastos, Andressa Ellen; Souza, Gabriela Azevedo; Fagundes, Alexandre Borges; Beuren, Fernanda Hänsch; Vaz, Caroline Rodrigues (Revista de Gestão Social e Ambiental, 2025)
THIS IS AN ARTICLE PUBLISHED BY Revista de Gestão Social e Ambiental (e-ISSN: 1981-982X) ON 2025-04-22, AVAILABLE ONLINE: https://doi.org/10.24857/rgsa.v19n4-114 Abstract Objective: To identify the challenges faced in implementing reverse logistics and to emphasize the importance of inspection actions for its success, aiming to provide recommendations to guide future policy and administrative decisions to improve reverse logistics in Brazil. Theoretical Framework: This framework provides a national overview of reverse logistics, including the PNRS and SINIR, and contextualizes the importance of inspection actions and ongoing initiatives at both national and state levels. It also highlights actions taken in Santa Catarina and shares the success story of CETESB (SP). Methodology: The methodology employed involved exploratory qualitative research, combining observation, reflection, and interpretation to examine the significance of inspection actions in Brazilian reverse logistics. Results and Discussion: The study highlights gaps in the inspection and organization of reverse logistics in Brazil, emphasizing the need for more effective public policies. CETESB in São Paulo demonstrates success with progressive regulations, while other states implement fragmented models, such as the initiatives under development in Santa Catarina. Research Implications: This study aims to serve as a starting point for broader discussions on reverse logistics, emphasizing the importance of monitoring as a key element in improving the effectiveness of these practices, and highlighting its crucial role in a context where the success of environmental policies is increasingly necessary. Originality/Value: The research is notable for its potential to impact public policies and advance social awareness.
Keywords: Reverse Logistics; Monitoring; CETESB; Santa Catarina; Success Story; National Panorama